Infigratinib (BGJ398) in previously treated patients with advanced or metastatic cholangiocarcinoma with FGFR2 fusions or rearrangements: mature results from a multicentre, open-label, single-arm, phase 2 study. (October 2021) - Javle, Milind; Roychowdhury, Sameek; Kelley, Robin Kate; Sadeghi, Saeed; Macarulla, Teresa; Weiss, Karl Heinz; Waldschmidt, Dirk-Thomas; Goyal, Lipika; Borbath, Ivan; El-Khoueiry, Anthony; Borad, Mitesh J; Yong, Wei Peng; et al.
Summary: Background: Treatment options are sparse for patients with advanced cholangiocarcinoma after progression on first-line gemcitabine-based therapy. FGFR2 fusions or rearrangements occur in 10–16% of patients with intrahepatic cholangiocarcinoma. Infigratinib is a selective, ATP-competitive inhibitor of fibroblast growth factor receptors. We aimed to evaluate the antitumour activity of infigratinib in patients with locally advanced or metastatic cholangiocarcinoma, FGFR2 alterations, and previous gemcitabine-based treatment. Methods: This multicentre, open-label, single-arm, phase 2 study recruited patients from 18 academic centres and hospitals in the USA, Belgium, Spain, Germany, Singapore, Taiwan, and Thailand. Eligible participants were aged 18 years or older, had histologically or cytologically confirmed, locally advanced or metastatic cholangiocarcinoma and FGFR2 fusions or rearrangements, and were previously treated with at least one gemcitabine-containing regimen. Patients received 125 mg of oral infigratinib once daily for 21 days of 28-day cycles until disease progression, intolerance, withdrawal of consent, or death. Radiological tumour evaluation was done at baseline and every 8 weeks until disease progression via CT or MRI of the chest, abdomen, and pelvis. The primary endpoint was objective response rate, defined as the proportion of patients with a best overall response of a confirmed complete or partial response, as assessed by blinded independent central review (BICR) according to Response Evaluation Criteria in Solid Tumors, version 1.1. The primary outcome and safety were analysed in the full analysis set, which comprised all patients who received at least one dose of infigratinib. This trial is registered with ClinicalTrials.gov, NCT02150967, and is ongoing. Findings: Between June 23, 2014, and March 31, 2020, 122 patients were enrolled into our study, of whom 108 with FGFR2 fusions or rearrangements received at least one dose of infigratinib and comprised the full analysis set. After a median follow-up of 10·6 months (IQR 6·2–15·6), the BICR-assessed objective response rate was 23·1% (95% CI 15·6–32·2; 25 of 108 patients), with one confirmed complete response in a patient who only had non-target lesions identified at baseline and 24 partial responses. The most common treatment-emergent adverse events of any grade were hyperphosphataemia (n=83), stomatitis (n=59), fatigue (n=43), and alopecia (n=41). The most common ocular toxicity was dry eyes (n=37). Central serous retinopathy-like and retinal pigment epithelial detachment-like events occurred in 18 (17%) patients, of which ten (9%) were grade 1, seven (6%) were grade 2, and one (1%) was grade 3. There were no treatment-related deaths. Interpretation: Infigratinib has promising clinical activity and a manageable adverse event profile in previously treated patients with locally advanced or metastatic cholangiocarcinoma harbouring FGFR2 gene fusions or rearrangements, and so represents a potential new therapeutic option in this setting. Funding: QED Therapeutics and Novartis.